To kontekster - to skrivepraksiser? Skriving i skole og bedrift i fag- og yrkesopplæringen [Two contexts - two writing practices? Writing in school and enterprises of Technical and Vocational Education and Training] - Ellen Beate Hellne-Halvorsen (Nordic Journal of Vocational Education and Training, 2019)
The topic of this article is literacy and writing practices in Technical and Vocational Education and Training (TVET). In Norway, TVET is organised as two years in school context followed by two years in enterprise. Based on a socio-cultural theoretical approach, the research question is: How is writing practiced in school and enterprise - as similar or as different practices? Writing skills are integrated in curriculum and part of vocational competences. Teachers and trainers are committed to work with and develop writing skills to students and apprentices. Different contexts may imply different writing practices by transfer and transformation from school to enterprises. My research shows that this is not the case, as writing in both contexts is mainly mediating learning outcomes from the school-based curriculum and not related to writing competences required in work life. The main purpose of writing practices is to assess and control skills and knowledge, related to vocational specific terminology and argumentation. Teachers and trainers appear to be main target group and not writing to different target groups in students' and apprentices' future working life as trained workers. These findings also indicate that generic or trans-contextual writing skills are not prioritized in neither of these contexts.